Analysis of modern facing techniques of plate edges - Bilyy, Yaroslav; Voytovych , Ivan; Grabar , Ivan (Forestry, Forest, Paper and Woodworking Industry, 2017)
A detailed analysis of the technological processes of touching the edges of the shield elements with the use of various lychello material on different technological equipment has been carried out. The technology of the faces of the edges of the shield elements is analyzed. A comparative analysis of the three technological processes of touching the edges of the panel elements has been fulfilled. The general methodology of researches of technological processes of facelift of edges of shield elements is developed. Materials for three types of castings of shield parts are calculated. The basic equipment according to the developed manufacturing technologies for the three variants of touching the edges of the panel elements is calculated. Three plans of shops have been developed. The analysis of the load of equipment for each variant of touching the edges of panel elements is carried out. The rational technologies of touching the edges of panel elements are selected based on the results of partial economic efficiency. It is recommended to introduce the optimal version number 3 of the technological process of rubbing the edges at the price of equipment 273 thousand UAH, the number of employees at the site of 5 people, and the capacity of equipment 15.9 kW.